Stability study in different hybrids of rabi sunflower (Helianthus annuus L.): STABILITY STUDY IN DIFFERENT HYBRIDS OF RABI SUNFLOWER - P S BELHEKAR; A M LANGHI; R D LOKHANDE; D N DAMSE (Journal of Oilseeds Research, 2025)
In present investigation the adapt ability of sixteen different hybrids along with two hybrid checks were studied for the characters seed yield per plot (g), head diameter (cm) and 100 seed weight (g) over eight different environments. The Genotype and Genotype x Environment interactions were found significant for all the characters indicating the presence of genetic variability in the hybrid population. The non-significant G x E (linear) interaction for all the characters when tested against pooled deviation indicated unpredictable performance of hybrids over the environment. The environmental indices revealed that, E8 was the favourable environment for seed yield per plot (g) and head diameter (cm), however E3 was favourable for 100 seed weight (g). For stability parameter, none of the hybrid was ideal with an average stability for all the traits. The hybrid SVSH-527 had high mean (u) for seed yield per plot (g) than hybrid mean, bi value nearer to unity (bi=1) and non-significant S 2di indicated average stability and suitable for all environment for seed yield per plot. Based on mean performance, hybrids SVSH-527, SVSH-528 and check Phule Raviraj for seed yield per plot, hybrids SVSH-518, SVSH-520, SVSH-523, SVSH-524, SVSH-526, SVSH-527 and check Phule Raviraj for head diameter (cm) and for 100 seed weight hybrid SVSH-527 showed stable performance.